2019
DOI: 10.1002/ijch.201900012
|View full text |Cite
|
Sign up to set email alerts
|

In Search of Bioactivity – Phyllobilins, an Unexplored Class of Abundant Heterocyclic Plant Metabolites from Breakdown of Chlorophyll

Abstract: The fate of the green plant pigment chlorophyll (Chl) in de‐greening leaves has long been a fascinating biological puzzle. In the course of the last three decades, various bilin‐type products of Chl breakdown have been identified, named phyllobilins (PBs). Considered ‘mere’ leftovers of a controlled biological Chl detoxification originally, the quest for finding relevant bioactivities of the PBs has become a new paradigm. Indeed, the PBs are abundant in senescent leaves, in ripe fruit and in some vegetables, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 102 publications
(190 reference statements)
0
14
0
Order By: Relevance
“…Among these are yellow phyllobilins (YCCs and DYCCs), first described in 2008 ( Moser et al , 2008b ) and 2019 ( Li et al , 2019 ), respectively, and now classified as phylloxanthobilins, which are readily oxidized further to the corresponding pink products (PiCCs and DPiCCs, classified as phylloroseobilins) ( Kräutler, 2016 ). The phyllochromobilins promise to have interesting biological properties, contrasting with the earlier characterization of the chlorophyll breakdown pathway as a mere detoxification mechanism ( Moser and Kräutler, 2019 ; Karg et al , 2020 ).…”
Section: Phyllobilin Diversity and Complexitymentioning
confidence: 90%
“…Among these are yellow phyllobilins (YCCs and DYCCs), first described in 2008 ( Moser et al , 2008b ) and 2019 ( Li et al , 2019 ), respectively, and now classified as phylloxanthobilins, which are readily oxidized further to the corresponding pink products (PiCCs and DPiCCs, classified as phylloroseobilins) ( Kräutler, 2016 ). The phyllochromobilins promise to have interesting biological properties, contrasting with the earlier characterization of the chlorophyll breakdown pathway as a mere detoxification mechanism ( Moser and Kräutler, 2019 ; Karg et al , 2020 ).…”
Section: Phyllobilin Diversity and Complexitymentioning
confidence: 90%
“…Thus, the discovery of the natural yellow-and pink-coloured PBs induced a first, decisive, consideration of their possible biological function as coloured pigments [11,31]. In more recent years, a number of biological roles have been suggested for the natural PBs [4,32], e.g., in signalling [33,34], as highly effective polar antioxidants [32,35], as metal chelators [21,28], as potential chromophores, and as inhibitors of the biosynthetic assembly of photoreceptors [4]. The striking blue luminescence of the colourless fluorescent Chl-catabolites [36], specifically of their persistent 'hypermodified' type (discovered in bananas [33,37]), may serve the communication between plants and (frugivorous) animals [4,36].…”
Section: E Ementioning
confidence: 99%
“…The degradation of the Chls in higher plants involves, roughly, 1000 million tons each year [1]. Thus, the natural Chl-breakdown via the PaO/phyllobilin pathway generates massive amounts of diverse PBs [7,8], polar natural products with remarkable heterocyclic structures [4,5,31], whose potential for a range of interesting biological roles should not be overlooked [23,32,38]. At various developmental stages, especially during leaf senescence [39] and fruit ripening [35,40], plant cells are 'flooded' with Chl-catabolites.…”
Section: E Ementioning
confidence: 99%
“…However, these properties do not fully illustrate/predict their biological effects in the cell; therefore, it is necessary to evaluate different heterocycle subtypes and consider their impact on biological systems. Heterocyclic compounds also occur in the environment as part of plant secondary metabolites [ 3 , 4 ] and show various effects, including in vitro cytotoxicity towards some cancer cell lines [ 5 ]. Many other heterocyclic compounds with high biological importance, such as serotonin, histidine, etc., are spread in the human organism.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that rel - N -(2,4-dichlorophenyl)-2-[(5aR,11bR)-2-oxo-5a,11b-dihydro-2 H ,5 H -chromeno[4′,3′:4,5]thiopyrano[2,3- d ][ 1 , 3 ]thiazol-3(6 H )-yl]acetamide (Les-2194), 5,10-dihydro-2 H -benzo[ 6 , 7 ]thiochromeno[2,3- d ][ 1 , 3 ]thiazole-2,5,10-trione (Les-3377), and 3-{2-[5-(4-dimethylaminophenyl)-3-phenyl-4,5-dihydropyrazol-1-yl]-4-oxo-4,5-dihydro-1,3-thiazol-5-ylidene}-2,3-dihydro-1 H -indol-2-one (Les-3640) exerted a high toxic effect on human squamous carcinoma cells (SCC-15). They were found to act mainly in a PPARγ-dependent manner [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%